(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Introduction: School based health interventions are a key setting in which to address health inequalities and health deficits of young people and future adult populations. Co- methodologies are being promoted as a ‘best buy’ approach to developing interventions that are contextually relevant and that may ultimately enable the intended behaviour change. Co- approaches, including co-production, co-design, and co-creation, are however terms used without any one single definition, and what these mean in practice varies widely. In secondary schools, a school’s competing priorities can make implementing co- approaches challenging. The aim of this rapid review was to examine the use of the co-production, co-design, and co-creation approaches in a secondary school setting. Specifically, it reports on co- approaches adopted, the framework used to inform the process, details of the methods, and the experience of the stakeholders involved. Methods: Following the guidelines for rapid reviews (Kings et al., 2022), studies that explicitly used the terms co-production, co-design, or co-creation in the design of health behaviour change interventions in secondary schools were included. PubMed and ERIC were searched in September 2024. Results: A total of 1,189 studies were identified, and following screening, six were included. Studies were conducted in the United States (n = 2), Ireland, Australia, Germany, and other parts of Europe. Four studies focused on wellbeing and mental health and two on physical health through physical activity. Five studies described the process adopted as co-creation and one as co-design. Only one study attempted to provide a definition of the co- approach adopted and whilst two studies investigated stakeholder experiences of the co- approach process, only one study reported these data. The studies used a range of frameworks to guide the co- approach activities including the double diamond framework, COM-B model, living lab approach, process-based counselling framework and UPRIGHT framework. They involved a narrow range of stakeholders that included families, pupils, teachers, and volunteers at different stages of the co- approach process. Conclusion: Each study engaged stakeholders differently at various stages of the co- approach process and with a wide range of activities. Co-creation was the term most commonly used, but what this meant for each study varied, and evaluation of the co- approach was rarely reported.